Analysis of bubble dynamics and thermal destratification induced by gas bubbles in cylindrical liquid storage tanks. (1st December 2022) - Sarath, Raj; Jayakumar, J.S.
Highlights: OpenFOAM code is modified to incorporate temperature-dependent transport properties. A new parameter to estimate the extent of the destratification is introduced. The destratification index increased by 25.29% as the diameter ratio is increased. Bubble in square pitch with p/d  = 4 gives higher effectiveness for thermal destratification. The destratification index increased by 44.65% as the gravity ratio is increased. Abstract: Thermal stratification is of great concern for liquid propellant storage tanks of space vehicles. The present study's primary objective is to better understand the bubble dynamics on thermal destratification, quantify the extent of destratification and propose a scheme for destratification. This study investigates the effect of different geometric parameters on the destratification of thermally stratified layers of liquid using the volume of fluid and interface compression method of OpenFOAM CFD code. The OpenFOAM code is modified to incorporate temperature-dependent fluid properties. Different values of bubble diameter, spacing between the bubbles, and arrangement of bubbles in triangular and square fashion with different pitches are considered. The effect of gravitational forces on thermal destratification is also reported. For all these cases, the effectiveness of thermal destratification is quantified in terms of the destratification index ( Id ). The average destratification index ( Idavg ) value increased by 25.29% as the ratio of bubble diameter to tank diameter ( d/D ) increased from 0.10 to 0.16. When the pitch to bubble diameter ratio ( p/d ) of triangular and square arrangements is reduced from 8 to 4, the Idavg increases by 14.59% and 22.97%, respectively. The average destratification index increased by 44.65% when the g/ge ratio changed from 0.3 to 3. These studies give an overall idea of the sparger design for getting the correct gas flow rate for thermal destratification within the liquid propellant storage tanks.